Development of a Web-Based Student Grade Information System as a System for Processing Student Grades and Monitoring Student Progress at SMK Negeri 1 Mondokan - Ananda Mutiara Sari; Arif Setiawan (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2024)
Implementing a website-based information system as a system for processing student grades is a way to facilitate monitoring of student progress. Monitoring activities have a very important role for teachers, students, and parents/guardians. By implementing website-based student assessments, the system for processing student grades is recorded manually using spreadsheets. This research uses research and development methods through the application of four method stages, namely exploration, development, testing, and dissemination. The results of implementing a website-based information system as a student grade processing system aim to create a website-based assessment system, a precise and accurate student grade processing system. The research results show that the use of a website-based student assessment system can speed up the teacher's work in monitoring student development. Apart from that, it can make it easier for parents to monitor their students at school. The use of a website-based assessment system has proven effective in monitoring student progress. Therefore, it can be concluded that a website-based assessment system can be a useful system in the world of education, especially for monitoring student progress in school